Delayed graft function on kidney transplant recipients - Rubén Schiavelli; Josefina Rosés; Daniel Di Tullio; Agustina Gautos; Roberto Sabbatiello; Mauricio Pattin; Miguel Raño (Revista de Nefrología, Diálisis y Trasplante, 2017)
Introduction: Delayed graft function (DGF) is a common complication in renal transplant and has implications for its development. Objectives: To know its incidence in a single transplant center, to describe the risk factors in donor and recipient, the procedure and the evolution of the graft and recipient. Methods: 178 renal transplant patients (P) with grafts from cadaveric donors were studied. Delayed graft function was defined as dialysis requirement in the first week post transplantation. We analyzed risk factors in the donor and recipient as well as the transplant procedures. Results: DGF incidence was 75.8% (135 patients). Risk factors for DGF were: greater cold ischemia time in minutes (1389 vs. 1224; P=0.01), greater recipient’s age in years (47.24 vs 40.71; P=0.001) and greater BMI of the donor (27.5 vs 25.17; P= 0.001). In 170 patients the presence of rejection was evaluated: those who had DGF presented more rejections (35.6% vs. 19.5%; P=0.046). The group with DGF showed lower graft survival at 5 years (P=0.0473), there was no difference in patient survival. Conclusion: The DGF incidence is higher than reported in the literature. Efforts should be made to reduce its incidence, focusing in reducing cold ischemia and improving maintenance of the donor.